The Influence of Work Discipline and Leadership Style on Employee Performance Through Work Effectiveness - Franklin Benedick; Hendratmoko Hendratmoko; Elisabeth Vita Mutiarawati (Jurnal Komunikasi dan Bisnis, 2025)
This research aims to analyze the influence of work discipline and leadership style on employee performance through work effectiveness. Research was conducted on employees of PT. Elektrindo Sarana Abadi. The sampling technique used saturated sampling with a total of 60 respondents. The research uses Structural Equation Modeling (SEM) using smartPLS 4.0. The research results show that work discipline has a positive and significant influence on work effectiveness. Leadership style has no effect on work effectiveness. Work discipline has a significant positive effect on employee performance. Leadership style has no effect on employee performance. Work effectiveness has a positive and significant influence on employee performance. Work discipline influences employee performance through work effectiveness. Leadership style does not affect employee performance through work effectiveness.